DiaSurg 2 trial - surgical vs. medical treatment of insulin-dependent type 2 diabetes mellitus in patients with a body mass index between 26 and 35 kg/m²: study protocol of a randomized controlled multicenter trial - DRKS00004550 - Kenngott, Hannes Götz; Clemens, Gabriella; Gondan, Matthias; Senft, Jonas; Diener, Markus K.; Rudofsky, Gottfried; Nawroth, Peter Paul; Büchler, Markus W.; Fischer, Lars; Müller, Beat P. (Trials, 2013)
Type 2 diabetes mellitus (T2DM) is a disease with high prevalence, associated with severe co-morbidities as well as being a huge burden on public health. It is known that glycemic control decreases long-term morbidity and mortality. The current standard therapy for T2DM is medical treatment. Several randomized controlled trials (RCTs) performed in obese patients showed remission of T2DM after bariatric surgery. Recent RCTs have shown bariatric procedures to produce a similar effect in non-morbidly and non-severely obese, insulin-dependent T2DM patients suggesting procedures currently used in bariatric surgery as new therapeutical approach in patients with T2DM. This study aims at investigating whether Roux-en-Y gastric bypass (RYGB) is an efficient treatment for non-severely obese T2DM patients in terms of preventing long-term complications and mortality.